Clinicopathological features of pyloric gland adenomas of the duodenum: a multicentre study of 57 cases. Issue 3 (1st December 2019) - Miller, Gregory C; Kumarasinghe, Marian P; Borowsky, Jennifer; Choi, Won‐Tak; Setia, Namrata; Clauditz, Till; Gidwani, Raja; Sufiyan, Wajiha; Lauwers, Gregory Y; Brown, Ian S
Abstract : Aims: To determine the clinicopathological features of pyloric gland adenomas (PGA) that arise in the duodenum. Methods and results: Fifty‐seven cases of duodenal PGA were identified and analysed from 56 patients. Clinicopathological and immunohistochemical analyses were performed. PGA tend to occur in older individuals (median age = 73.5), with a slight female predominance (25 males, 31 females). PGA arise more commonly in the proximal duodenum (68.75% in D1, 25% in D2 and 6.25% in D3) and usually present as mucosal nodules (98.2%) or plaques (1.8%), with a mean size of 14.8 mm. There is associated gastric heterotopia in 22.8% of cases. PGA showing features of high‐grade dysplasia were significantly larger in size than PGA, showing only low‐grade dysplasia (23.1 versus 8.7 mm; P =  0.0001) and more likely to show a tubulovillous rather than a pure tubular architecture ( P =  0.025). In our series, 10 of 56 patients had intramucosal or invasive carcinoma associated with the duodenal PGA (17.9%). Three of these carcinomas showed lymph node metastasis. Following definitive treatment, local recurrence occurred in only three patients. Conclusions: Duodenal PGA tend to occur in the proximal duodenum of older individuals. Larger size and tubulovillous architecture correlates with high‐grade dysplasia and associated adenocarcinoma. The low recurrence rate of these lesions would suggest that endoscopic management is appropriate, provided that the lesion can be completely resected.